Improvement of thermoelectric properties of Bi2Te3 and Sb2Te3 films grown on graphene substrate - Lee, Chang Wan; Kim, Gun Hwan; Choi, Ji Woon; An, Ki-Seok; Kim, Jin-Sang; Kim, Hyungjun; Lee, Young Kuk (WILEY-V C H VERLAG GMBH, 2017)
A study of substrate effect on the thermoelectric (TE) properties of Bi2Te3 (BT) and Sb2Te3 (ST) thin films grown by plasma-enhanced chemical vapor deposition (PECVD) was performed. Graphene substrates which have small lattice mismatch with BT and ST were used for the preparation of highly oriented BT and ST thin films. Carrier mobility of the epitaxial BT and ST films grown on the graphene substrates increased as the deposition temperature increased, which was not observed in that of SiO2/Si substrates. Seebeck coefficients of the as-grown BT and ST films were observed to be maintained even though carrier concentration increased in the epitaxial BT and ST films on graphene substrate. Although Seebeck coefficient was not improved, power factor of the as-grown BT and ST films was considerably enhanced due to the increase of electrical conductivity resulting from the high carrier mobility and moderate carrier concentration in the epitaxial BT and ST films. (C) 2017 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim
Keywords: THIN-FILM; SUPERLATTICE STRUCTURES; POWER-GENERATION; DEPOSITION; ENHANCEMENT; TELLURIUM; DEVICES; MOCVD